Platelet-to-Lymphocyte Ratio as a Potential Diagnostic Marker for Acute Coronary Syndromes in Resource-Limited Settings: A Cross-Sectional Study from Single Center in Banten, Indonesia - Mubarak, Thariq; Mervina Yulih Cania; Hafiz Mirza Fadrian (HM Publisher, 2024)
Background: Acute coronary syndrome (ACS) poses a significant global health burden, particularly in resource-limited settings where access to advanced diagnostic tools is often constrained. The platelet-to-lymphocyte ratio (PLR), a simple and readily available marker from routine blood tests, has shown promise as a potential diagnostic tool for ACS. This study aimed to evaluate the diagnostic accuracy of PLR in identifying ACS patients in a resource-limited setting in Indonesia. Methods: A cross-sectional study was conducted at Hermina Periuk Hospital, Tangerang, Banten, Indonesia, between December 2020 and December 2022. Patients presenting to the Emergency Room with a diagnosis of ACS were included. PLR was calculated from complete blood count data, and cardiac troponin I (cTnI) served as the gold standard for ACS diagnosis. The diagnostic performance of PLR in predicting elevated cTnI levels was assessed. Results: Of the 121 patients initially identified, 39 met the inclusion and exclusion criteria. Elevated PLR values (>116) were observed in 25 patients (64.1%), while 15 patients (38.5%) had elevated cTnI levels. A statistically significant correlation was found between elevated PLR and elevated cTnI (p = 0.018). No significant association was observed between neutrophil-to-lymphocyte ratio (NLR) and elevated cTnI. Conclusion: PLR demonstrates potential as a diagnostic marker for ACS in resource-limited settings. Its simplicity, accessibility, and cost-effectiveness make it a valuable tool for early identification and risk stratification of ACS patients, particularly in areas with limited access to advanced cardiac diagnostics.